Evaluating Agricultural Extension Frameworks in Resource-Constrained Regions: Strengths and Weaknesses - Kobusiingye, Florah; Ssembatya, Richard; Kaggwa, Fred; Ejiri, Annabella Habinka (European Journal of Science, Innovation and Technology, 2024)
Agricultural extension frameworks are crucial in enhancing farming practices and improving livelihoods in resource-constrained regions. This study evaluates five prominent agricultural extension frameworks: Farmer Field School (FFS), Problem-Based Learning (PBL), Training of Trainers (ToT), Agricultural Knowledge and Information System (AKIS), and Farmer-to Farmer Extension (F2FE) to identify their strengths and weaknesses. The analysis reveals that while each framework has merits such as participatory learning and scalability, they also face challenges including resource intensity and limited reach. This paper proposes a hybrid model integrating the strengths of these frameworks while addressing their limitations, aiming to provide a more effective agricultural extension system for regions like Uganda.
Keywords: Agricultural extension frameworks; Enhancing farming practices; Improving livelihoods; Resource-constrained regions